2008
DOI: 10.1037/0882-7974.23.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Comparing memory skill maintenance across the life span: Preservation in adults, increase in children.

Abstract: The authors examined life-span differences in the maintenance of skilled episodic memory performance by assessing 100 individuals (10 -11, 12-13, 21-26, and 66 -79 ). Skill maintenance was tested in 2 follow-up sessions, the first without and the second with mnemonic reinstruction. Younger and older adults' average performance levels were stable across time. In contrast, both younger and older children's memory performance improved beyond originally attained levels. Older adults' performance improved from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 98 publications
(135 reference statements)
3
51
0
Order By: Relevance
“…In spite of these results, a multifactor approach can be more complete. If the aim of the study is to change beliefs and stereotypes about cognitive function in the elderly, the research should include these aspects in the program (Brehmer et al, 2008).…”
Section: Multifactorial or Traditional Memory Training In Agingmentioning
confidence: 99%
“…In spite of these results, a multifactor approach can be more complete. If the aim of the study is to change beliefs and stereotypes about cognitive function in the elderly, the research should include these aspects in the program (Brehmer et al, 2008).…”
Section: Multifactorial or Traditional Memory Training In Agingmentioning
confidence: 99%
“…One study by Fairchild, Friedman, Rosen, and Yesavage (2013), demonstrated that higher associative memory scores and lower training gains were associated with better maintenance one year later. Studies that involved a direct comparison of younger and older adults (Brehmer et al, 2008) or associations between age and maintenance within an older sample (O'Hara et al, 2007), indicate that maintenance is largely spared by the ageing process. In turn, this might suggest that cognitive factors such as working memory and processing speed play a limited role in explaining individual differences in durability in response to mnemonic training.…”
Section: Introductionmentioning
confidence: 99%
“…Complex mental activity can promote several neuroplastic mechanisms, a phenomenon that is conserved well into advanced age [1] and hence may be exploited for the mitigation of age-related changes in cognition. For example, meta-analyses have shown that individuals with higher levels of mental activity are at only about half the risk of developing dementia [2] and have a reduced rate of incident cognitive decline [3], and that late-life mental exercise exhibits a dose-dependent relationship with dementia risk reduction independent of early life experiences [2].…”
Section: Introductionmentioning
confidence: 99%